Bankers' compensation and fair value accounting - Livne, Gilad; Markarian, Garen; Milne, Alistair (Journal of Corporate Finance, 2011)
This paper examines the role of certain fair value accounting (FVA) outcomes in compensation of US bank CEOs. The use of FVA in compensation invites an agency cost—the clawback problem—if cash compensation is based on unrealized profits that may reverse in the future. At the same time FVA may be a good measure of current managerial effort and so be cash compensated. We find evidence consistent with a positive link between CEO cash bonus and fair value (FV) valuation of trading assets, managed for short-term profit, as well as (amongst banks with limited trading exposure) a positive link between CEO pay and FV valuations of available for sale (AFS) assets. We find no evidence that trading income is incrementally compensation relevant, indicating that compensation committees avoided the clawback problem for unrealized trading gains. The paper also provides evidence on the link between FVA outcomes and equity-based pay.